Synthesis and Characterization of CNT/PVA Nanocomposites for Electrical, Thermal and Morphological Properties - Nasar, Gulfam; Khalil, Uzma; Khan, Muhammad Saleem; Nadeem, Qaisar (Journal of Materials and Physical Sciences, 2022)
The goal of the current work is to bring a helpful substance to nanoscience and nanotechnology that might be a "problem solver" for ion storage. Carbon nanotubes/ PVA nanocomposites were prepared in five concentrations in aqueous medium following film formation. The resulting nanocomposites were characterized using “AC Impedance Spectroscopy, Differential Thermal Analysis, Thermal Gravimetric Analysis / (TG/DTA) and Scanning Electron Microscopy (SEM)”. Ionic conductivity of the nanocomposites was determined from impedance spectroscopy. CNT/PVA nanocomposites exhibited lower conductivity as compared with CNT or PVA separately. TG/DTA graphs exhibited a regular pattern, showing an increase in the thermal stability. Morphology of the prepared samples as shown by SEM reveals a favourable polymer-filler morphological arrangement at the interphase, which is suggestive of a favourable compatibility between the polymer and the filler substance.